Failure and stress analysis of through-aluminum-nitride-via substrates during thermal reliability tests for high power LED applications. (December 2016) - Tsai, M.Y.; Lin, C.H.; Chuang, K.F.; Chang, Y.H.; Wu, C.T.; Hu, S.C.
Abstract: The objective of this study is to evaluate the reliability of through-aluminum-nitride-via (TAV) substrate by comparing those experimental results with the finite element simulation associated with measurements of aluminum nitride (AlN) strength and the thermal deformation of Cu/AlN bi-material plate. Two reliability tests for high-power LED (Light emitting diode) applications are used in this study: one is a thermal shock test from − 40 °C to 125 °C, the other is a pressure cook test. Also, the strength of AlN material is measured by using three-point bending test and point load test. The reliability results show that TAV substrates with thicker Cu films have delamination and cracks after the thermal shock test, but there are no failure being found after the pressure cook test. The determined strengths of AlN material are 350 MPa and 650 MPa from three-point bending test and point load test, respectively. The measurement of thermal deformation shows that the bi-material plate has residual-stress change after the solder reflow process, also indicating that a linear finite element model with the stress-free temperature at 80 °C can reasonably represent the stress state of the thermal shock test from − 40 °C to 125 °C without considering Cu nonlinear effect. The further results of the finite element simulation associated with strength data of AlN material have successfully described those of the reliability test. Highlights: Delamination and cracks in TAV substrates were found after TS, but no failure after PCT. Strengths of AlN are 350 and 650 MPa from 3-point bending and point load tests, respectively and insensitive to TS and PCT. Thermal deformations of a bi-material plate provide residual stress and stress-free temperature during TS test. A linear finite element model reasonably represents the stress state of the TS test. The finite element results with AlN strength data successfully describe those of the reliability test.